Avaliação de métodos de conservação e processamento de amostras de urina de bovinos e ovinos para analisar creatinina, ureia e derivados de purina - Santos, Fabiene Tomazetti dos (2019)
The objective of this study was to evaluate the impact of the method of preservation, sample processing and conservation time on the concentration of metabolites in urine samples from cattle and sheep. 112 samples of urine of dairy cattle and 42 samples of castrated male sheep were collected. Urine samples were added with either storage media: acid medium (sulfuric acid), basic medium (sodium hydroxide), medium without preservative (distilled water). The effect of the exposition to the environmental temperature during 12 hours before stored frozen, and the sonication processing of samples before analysis on metabolites concentration was evaluated in some sheep urine samples. The metabolites concentration were determined using colorimetric techniquesy. The urea concentration was not affected by method of preservation. The concentration of creatinine and uric acid were lower whereas de allantoin was higher in samples added with basic solution (P<0,05). The sonication resulted in higher values of allantoin (P<0,05) whereas it didi not affect the concentration of other metabolites. Independently of preservation method, the exposition of samples to the environment temperature for 12 hours did not affect the concentration of any metabolite. In conclusion, results of the presente study indicated that there was not need of using any type of preserving solution in urine samples for determining the excretion of creatinine, urea or uric acid, whereas a basic solution should be added for determining the excretion of allantoin. In addition, sonication of samples is a recommended procedure before analysis, mainly of allantoin.